ANALISIS HAK ANAK AKIBAT KAWIN HAMIL DITINJAU DARI HIFDZU NASAB DALAM MAQASHID SYARIAH - Dewi, Nirwana (Program Studi Hukum, Universitas Muhammadiyah Sukabumi, 2025)
Out-of-wedlock pregnancies occur as a result of pregnancies before a valid marriage, which is considered adultery. The Marriage Law states that a marriage is valid if it is in accordance with the laws of the relevant religion. In Islamic law, legal marriage must meet existing principles and provisions, as well as take into account harmony and relevant legal conditions. This study aims to examine the rights of children born of pregnancy from extramarital marriage in Sukabumi City. The method employed is a qualitative descriptive approach, utilizing field research to gather direct data on legal and social phenomena. The results of the study show that children born to pregnant marriages do not have harmony with their biological fathers, so they do not get inheritance and maintenance rights. As a result, the biological father has no legal obligation to provide for the child. Although many fathers provide sustenance through grants, this does not replace the inheritance rights that children should have. This research highlights the need for a better understanding of children's rights in the context of Islamic law and Marriage Law. It is hoped that this research can provide input for the formation of fairer policies for children resulting from pregnancies outside of legal marriage.